Survival Outcomes Among Patients With High-Grade Glioma Treated With 5-Aminolevulinic Acid–Guided Surgery: A Systematic Review and Meta-Analysis - Gandhi, Sirin; Tayebi Meybodi, Ali; Belykh, Evgenii; Cavallo, Claudio; Zhao, Xiaochun; Syed, Masood Pasha; Borba Moreira, Leandro; Lawton, Michael T.; Nakaji, Peter; Preul, Mark C. (Frontiers in Oncology, 2019)
Background: High-grade glioma (HGG) is associated with a dismal prognosis despite significant advances in adjuvant therapies, including chemotherapy, immunotherapy, and radiotherapy. Extent of resection continues to be the most important independent prognosticator of survival. This underlines the significance of increasing gross total resection (GTR) rates by using adjunctive intraoperative modalities to maximize resection with minimal neurological morbidity. 5-aminolevulinic acid (5-ALA) is the only US Food and Drug Administration–approved intraoperative optical agent used for fluorescence-guided surgical resection of gliomas. Despite several studies on the impact of intra-operative 5-ALA use on the extent of HGG resection, a clear picture of how such usage affects patient survival is still unavailable. Methods: A systematic review was conducted of all relevant studies assessing the GTR rate and survival outcomes [overall survival (OS) and progression-free survival (PFS)] in HGG. A meta-analysis of eligible studies was performed to assess the influence of 5-ALA-guided resection on improving GTR, OS, and PFS. GTR was defined as >95% resection. Results: Of 23 eligible studies, 19 reporting GTR rates were included in the meta-analysis. The pooled cohort had 998 patients with HGG, including 796 with newly diagnosed cases. The pooled GTR rate among patients with 5-ALA–guided resection was 76.8% (95% confidence interval, 69.1–82.9%). A comparative subgroup analysis of 5-ALA–guided vs. conventional surgery (controlling for within-study covariates) showed a 26% higher GTR rate in the 5-ALA subgroup (odds ratio, 3.8; P < 0.001). There were 11 studies eligible for survival outcome analysis, 4 of which reported PFS. The pooled mean difference in OS and PFS was 3 and 1 months, respectively, favoring 5-ALA vs. control (P < 0.001). Conclusions: This meta-analysis shows a significant increase in GTR rate with 5-ALA–guided surgical resection, with a higher weighted GTR rate ( 76%) than the pivotal phase III study ( 65%). Pooled analysis showed a small yet significant increase in survival measures associated with the use of 5-ALA. Despite the statistically significant results, the low level of evidence and heterogeneity across these studies make it difficult to conclusively report an independent association between 5-ALA use and survival outcomes in HGG. Additional randomized control studies are required to delineate the role of 5-ALA in survival outcomes in HGG.